2008
DOI: 10.1017/s0022381608080481
|View full text |Cite
|
Sign up to set email alerts
|

What's Good for the Goose is Bad for the Gander: Negative Political Advertising, Partisanship, and Turnout

Abstract: This study examines citizens' perceptions of fairness and legitimacy in political advertising. Using focus groups, an original national survey, and data on election 2000, as well as drawing on results from a replication of the national survey in 2004, we characterize political ads from the citizen's perspective. We then turn to the impact of ''negative'' advertising on voter turnout. Like several studies, we find circumstances under which turnout can be increased by negative ad criticisms. However, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…A substantial body of research suggests that information, including performance information cues, are unlikely simply to be neutrally received, processed, and acted on by citizens. Much research on political information examines the impact of different information sources and the characteristics of voters on the use of information (Gaines et al 2007;Lau and Redlawsk 2006;Lau et al 1999;Lodge, Steenbergen, and Brau 1995;Stevens et al 2008). The literature on media effects similarly suggests that the source and presentation of information affect its reception and use by citizens (Jerit, Barabas, and Bolsen 2006;Kuklinski et al 2001) and the effect of the editorial slant of the media during campaigns on voting outcomes has been noted (Druckman and Parkin 2005).…”
Section: Citizens and Public Service Performance Measuresmentioning
confidence: 99%
“…A substantial body of research suggests that information, including performance information cues, are unlikely simply to be neutrally received, processed, and acted on by citizens. Much research on political information examines the impact of different information sources and the characteristics of voters on the use of information (Gaines et al 2007;Lau and Redlawsk 2006;Lau et al 1999;Lodge, Steenbergen, and Brau 1995;Stevens et al 2008). The literature on media effects similarly suggests that the source and presentation of information affect its reception and use by citizens (Jerit, Barabas, and Bolsen 2006;Kuklinski et al 2001) and the effect of the editorial slant of the media during campaigns on voting outcomes has been noted (Druckman and Parkin 2005).…”
Section: Citizens and Public Service Performance Measuresmentioning
confidence: 99%
“…In accordance with the need to avoid a broad definition of negative campaigning (Richardson, ), research showed that differentiating between issue‐based and person‐based political attacks is essential to understand when a backlash effect is likely to occur. Issue‐based negative messages, that is, attacks bearing criticisms on political issues, are typically judged as fair attacks; on the contrary, person‐based negative messages, that is, attacks focused on personal characteristics of the opponent, are in contrast with social norms that prescribe fairness in interpersonal relations and are mostly evaluated as unfair play (Stevens, Sullivan, Allen, & Alger, ). In other words, attacking the opponent on personal issues is a norm‐violating behavior, whereas attacking on issue‐based topics is a norm‐consistent behavior in electoral campaigns.…”
Section: Negative Campaigns and Group Dynamicsmentioning
confidence: 99%
“…; Sigelman and Kugler ; Stevens ; Stevens et al . )—including, perhaps, beliefs about the trustworthiness of those who run, or who seek to run, the government. The literature provides us with uncertain guidance on this point.…”
Section: The Effectiveness Of Negative Ads: An Overviewmentioning
confidence: 99%
“…; Sides, Lipsitz, and Grossman ; Stevens et al . ). This complexity of opinion may help to explain why scholars have been unable to document a strong or consistent relationship between campaign negativity and feelings of trust directed at political institutions, authorities, and processes (Brooks and Geer ; Jackson, Mondak, and Huckfeldt ; Lau and Pomper ; but see Lau, Sigelman, and Rovner ; Stevens ).…”
mentioning
confidence: 97%